Design and end chamfer simulation of PEFP beam line curved dipole magnets - 朱应顺 杨梅 张卓 陈宛 尹宝贵 石才土 康文 (Chinese physics C, 2011)
The design, fabrication and field measurement of 11 DC curved dipole magnets for the PEFP Beam Line have been completed. In this paper, a design method for a complex end chamfer using OPERA-3D is proposed. The conventional method for estimating chamfer shape is extended and applied to a curved dipole magnet by a coordinate transformation. Using the interface with CAD software, the complex end chamfer is modeled and fully determined by 3D simulation to meet the field uniformity requirement. The magnetic field measurement results are in good agreement with the simulation. The design considerations, field simulation results, end chamfer development process and measurement results are presented in detail.